Wide-narrow row planting and limited irrigation improve grain filling and spike traits in winter wheat in arid regions - Jianghua Tang; Jingjing Lu; Chen Wang; Songhao Ge; Zhihua Chen; Yihong Wen; Liping Zhou; Tingting Sun; Wenxui Xu (Scientific Reports)
Abstract Winter wheat is a vital grain crop in Xinjiang and severe water scarcity in this arid region necessitates efficient irrigation strategies for sustainable production. A two-year field experiment (2022–2023) in northern Xinjiang was conducted to evaluate the effects of sowing patterns and drip irrigation levels on winter wheat growth and yield. Two sowing patterns were tested: uniform row spacing (CK1, 15 cm) and wide–narrow row spacing, comprising 13.3 cm + 13.3 cm + 13.3 cm + 20 cm (M1), 10 cm + 10 cm + 10 cm + 30 cm (M2), and 10 cm + 10 cm + 10 cm + 20 cm (M3). Four drip irrigation levels were applied: 4500 mm2/hm2 CK), 3600 m³/hm² (D1), 2700 m³/hm² (D2), and 0 m2/hm2 (D3). The results indicate that wide–narrow row spacing increased the single-plant dry matter weight, with the stem + sheath and spike allocation ratios at maturity increasing by 15.31% and 6.59%, respectively. Wide–narrow rows improved spike traits, particularly in the outer rows, increasing spike length and grain number per spike by 0.46% and 0.68%, respectively, and reducing sterile spikelets by 1.35%. Compared with the CK1D1 treatment, the M2D1 treatment significantly increased the number of spikes per unit area, number of grains per spike, and yield by 19.15%, 5.92%, and 19.10%, respectively, with no significant difference in thousand-kernel weight. These findings demonstrated that M2D1 treatment optimized yield and water-saving efficiency, providing critical guidance for winter wheat production in arid regions.